2023
DOI: 10.3390/ijms24129859
|View full text |Cite
|
Sign up to set email alerts
|

Circular Intronic RNA circTTN Inhibits Host Gene Transcription and Myogenesis by Recruiting PURB Proteins to form Heterotypic Complexes

Abstract: Muscle cell growth plays an important role in skeletal muscle development. Circular RNAs (circRNAs) have been proven to be involved in the regulation of skeletal muscle growth and development. In this study, we explored the effect of circTTN on myoblast growth and its possible molecular mechanism. Using C2C12 cells as a functional model, the authenticity of circTTN was confirmed by RNase R digestion and Sanger sequencing. Previous functional studies have showed that the overexpression of circTTN inhibits myobl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1
1

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 43 publications
0
2
0
Order By: Relevance
“…The expression level of mRNA was detected with high or significant differences, but different results were found when detecting the corresponding protein abundance. Resulting in the expression of mRNA measured by experiment is not consistent with the real protein situation (Ai et al, 2023;Wang et al, 2023;Yu et al, 2023). Existing literature also underscores the influence of age on gene expression levels in mammalian tissues (Ahn et al, 2019;Bloom et al, 2020).…”
Section: Introductionmentioning
confidence: 85%
“…The expression level of mRNA was detected with high or significant differences, but different results were found when detecting the corresponding protein abundance. Resulting in the expression of mRNA measured by experiment is not consistent with the real protein situation (Ai et al, 2023;Wang et al, 2023;Yu et al, 2023). Existing literature also underscores the influence of age on gene expression levels in mammalian tissues (Ahn et al, 2019;Bloom et al, 2020).…”
Section: Introductionmentioning
confidence: 85%
“…Notably, this group also uncovered that circ-SIRT1 contributed to stabilizing SIRT1 protein post-translationally via recruiting USP22 and further accelerating deubiquitination on SIRT1 protein [39]. Additionally, circTTN, a circular intronic RNA, was confirmed to repress the transcription and myogenesis of TTN through forming heterotypic complexes via recruiting PURB proteins [40]. An antisense circRNA, named circSCRIB, was illustrated to retard the splicing and translation of its parental gene SCRIB, enhancing BC progression [41].…”
Section: Affecting Parental Gene Expressionmentioning
confidence: 96%
“…Ai et al found differentially expressed circRNA (circTTN) in Ningxiang pig muscle tissue, and further veri ed its role in muscle development on cells. The results showed that circTTN inhibited host gene transcription and myogenesis by binding PURB protein [22]. However, these results still remain largely unclear for dissecting the mechanism of skeletal muscle development.…”
Section: Introductionmentioning
confidence: 98%